The Law and Governance of Decentralised Business Models: Between Hierarchies and Markets - Barker, Roger M; Chiu, Iris H-Y (Routledge Research in Corporate Law, 2021)
This book draws together themes in business model developments in relation to decentralised business models (DBMs), sometimes referred to as the 'sharing' economy, to systematically analyse the challenges to corporate and organisational law and governance. DBMs include business networks, the global supply chain, public-private partnerships, the platform economy and blockchain-based enterprises. The law of organisational forms and governance has been slow in responding to changes, and reliance has been placed on innovations in contract law to support the business model developments. The authors argue that the law of organisations and governance can respond to changes in the phenomenon of decentralised business models driven by transformative technology and new socio-economic dynamics. They argue that principles underlying the law of organisations and governance, such as corporate governance, are crucial to constituting, facilitating and enabling reciprocality, mutuality, governance and redress in relation to these business models, the wealth-creation of which subscribes to neither a firm nor market system, is neither hierarchical nor totally decentralised, and incorporates socio-economic elements that are often enmeshed with incentives and relations. Of interest to academics, policymakers and legal practitioners, this book offers proposals for new thinking in the law of organisation and governance to advance the possibilities of a new socio-economic future.